Crystal structure of tramadol hydrochloride, C16H26NO2Cl. Issue 3 (12th August 2015) - Kaduk, James A.; Zhong, Kai; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of tramadol hydrochloride has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Tramadol hydrochloride crystallizes in space group Cc (#9) with a = 9.680 72(2), b = 19.191 27(4), c = 9.285 94(1) Å, β = 100.5923(1)°, V = 1695.795(5) Å 3, and Z = 4. The solid-state conformation of the cation differs from the minimum-energy conformation of the tramadol cation in water, and from the conformation observed in the benzoic acid adduct of tramadol hydrochloride. N–H···Cl and O–H···Cl hydrogen bonds form a zigzag chain with graph set C 1, 2(8) along the c -axis. C–H···O hydrogen bonds also contribute to the crystal energy. The powder pattern has been submitted to ICDD for inclusion in the Powder Diffraction File™.